Pengaruh Model Pembelajaran Game Based Learning Berbantuan Media Memory Run Terhadap Hasil Belajar IPAS Siswa - Ni Luh Putu Pratiwi; I Gusti Ngurah Triyana; I Komang Wisnu Budi Wijaya (Alpatih Harapan Semesta, 2026)
Students often struggle to understand Science and Social Studies (IPAS) concepts, particularly the human respiratory system, due to uninnovative learning approaches and low participation. This study evaluates the impact of the Game Based Learning (GBL) model assisted by Memory Run media on fifth-grade students' learning outcomes. Anchored in John Dewey’s constructivism and Slavin’s motivation theory, this research argues that experiential, game-reinforced learning significantly enhances comprehension. A quantitative quasi-experimental method with a non-equivalent control group design was employed, utilizing multiple-choice objective tests as the instrument. The independent sample t-test yield a significance value (Sig. 2-tailed) of 0.002 < 0.05, confirming that the alternative hypothesis (Ha) is accepted. This proves that the Game Based Learning (GBL) model with Memory Run media significantly improves student learning outcomes. Elementary schools are highly recommended to implement this innovative model to foster active participation. Consequently, these findings imply that integrating digital or physical educational games into complex science topics can effectively bridge conceptual gaps in primary education